EVALUASI PERTUKARAN MAHASISWA MERDEKA BERBASIS MATA KULIAH MENGGUNAKAN PROVUS’S DISCREPANCY MODEL DENGAN DOUBLE SMART - M. Zainudin; Anita Dewi Utami (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
This study aims to describe the gaps among definitions, installations, processes, and products with standard operational criteria in the independent student exchange cooperation program. The study used Povus' discrepancy model. The subjects of this study involved lecturers and students from Universitas PGRI Madiun, IKIP PGRI Bojonegoro, Muhammadiyah University of Ponorogo, Muhammadiyah University of Kotabumi, STKIP PGRI Bangkalan, and STKIP Taman Siswa Bima. The data were collected through interviews, questionnaires, observation, and document analysis. Then, they were analyzed using descriptive qualitative, which was then compared with standard criteria. The results show that the student exchange program focused on course exchange at IKIP PGRI Bojonegoro, Universitas PGRI Madiun, Muhammadiyah University of Ponorogo, STKIP PGRI Bangkalan, and STKIP Taman Siswa Bima, i.e., design, installation, process, and products is following the guidelines for implementing the independent student exchange cooperation program. It was found that there was a gap in the program implementation process, but the program objectives had been achieved. Students who participated in the program were facilitated in developing science and technology, Wawasan Kebangsaan (national vision), nationalism, and the understanding of diversity, plurality, and tolerance from other universities. It was revealed that 85% of the students got an A predicate, and the rest got B in courses taken at other universities. Based on the implementation of double-smart, it is hoped that the independent student exchange cooperation program, which is focused on course exchange, can be continued with improvements.